The Translation of Onomatopoeia in Ariel Duyung’s Comic (Good/Bad Fortune) - Yuria, Hersa; Ardi, Havid (Universitas Negeri Padang, 2024)
Several aims have been established, including the examination of onomatopoeia types and the technique employed for translating onomatopoeia in the webtoon comic titled